Feeding ecology and habitat of the Protea seedeater Serinus leucopterus - Milewski, Antoni Vincent (Department of Biological Sciences, 2015)
The present study involved a description of the habitat and the feeding niche (sensu Whittaker et. al. 1973) of the protea seedeater, and an assessment of factors contributing to the ecological segregation between the protea seedeater and its congeners in the south-west Cape biotic zone. No similar study of an African bird has been attempted.